Hubungan Pola Menyikat Gigi dengan Karies Gigi - Ristya Widi Endah Yani (Faculty of Dentistry, Universitas Indonesia, 2015)
A cross-sectional investigation aimed to establish the relation between the pattern of tooth brushing and dental caries for a non-random (accidental) sample of 140 people, more than 12 years old, in PugerKulon village. The used instruments and materials were explorer, mouth mirror, deppen glass, neirbeken, 70% alcohol and a questionnaire sheet. The resulting data were analyzed by chi-square test (α=0.05). The results show a significant association of the pattern of tooth brushing with caries, so that an applied pattern of tooth brushing significantly decreased dental caries. Conversely, absent tooth brushing was significantly associated with higher incidence of caries.